1984
DOI: 10.1530/jrf.0.0720463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding melatonin to red deer (Cervus elaphus) on the onset of the breeding season

Abstract: Four non-lactating red deer hinds kept in natural light were each given orally 5 mg melatonin daily in the afternoon from 1 June to 5 October. The time difference between melatonin administration and sunset was 5.5-6 until the end of August, thereafter gradually decreasing to 3.5 h. Onset of oestrous cyclicity occurred in late August and early September, 2-8 weeks in advance of control hinds. A stag given 10 mg melatonin daily shed the antler velvet on 18 July, 4 weeks earlier than untreated stags, and started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
2

Year Published

1987
1987
1997
1997

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 7 publications
4
28
2
Order By: Relevance
“…The effects of continued daily administration of melatonin on the ovarian activity of cyclic red deer have not previously been recorded since administration of melatonin to anoestrous hinds in the summer has ceased once seasonal breeding activity has been initiated and conceptions have occurred (Adam & Atkinson, 1984;Webster & Barrell, 1985;Adam et ai, 1986). The prolonged stimulatory effect of melatonin on ovarian cyclicity in deer in this trial contrasts with its reported effects in sheep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of continued daily administration of melatonin on the ovarian activity of cyclic red deer have not previously been recorded since administration of melatonin to anoestrous hinds in the summer has ceased once seasonal breeding activity has been initiated and conceptions have occurred (Adam & Atkinson, 1984;Webster & Barrell, 1985;Adam et ai, 1986). The prolonged stimulatory effect of melatonin on ovarian cyclicity in deer in this trial contrasts with its reported effects in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In (Adam & Atkinson, 1984;Adam et al, 1986). The sensitivity of the assay was 0-2 ng/ml, and intra-and inter-assay coefficients of variation at 1-3 ng/ml were 9 and 13% respectively.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, in the ram, exposure to long days is necessary before rams can respond to melatonin implants (Lincoln & Ebling, 1985) while in the ewe, treatment with melatonin in January (Nett & Niswender, 1982) or April and May (Nowak & Rodway, 1985;English et al, 1986) is ineffective in inducing an early return to oestrus. In contrast, treatment with melatonin close to or after the mid¬ summer solstice is effective in inducing early breeding in the ewe (Kennaway et al, 1982;Arendt et al, 1983) and in seasonal deer (Bubenik, 1983;Adam & Atkinson, 1984;Lincoln et al, 1984). In this paper, we report the results of experiments designed to consider the effect of reductions in daylength or treatment with melatonin 1-2 months and 4-5 months after the winter solstice on the seasonal reproductive quiescence in the Bennett's wallaby.…”
Section: Introductionmentioning
confidence: 99%
“…T resumption of ovarian cyclicity in short-day breeders, ewes [1][2][3] and red deers [4][5][6]. Many studies in the mid-latitude regions have indicated that the resumption of the breeding season for non-lactating ewes administered melatonin occurred earlier than that in control ewes.…”
mentioning
confidence: 99%